Administración contable del comercial Díaz del cantón Alfredo Baquerizo Moreno (Jujan) 2022. - Díaz Ronquillo, Carmen (2022)
Within the present case study which was prepared with the purpose of determining how the accounting administration affects the development of the commercial Díaz in the Alfredo Baquerizo Moreno Jujan Canton in 2022. We used the method of methodological approach with which we can perform a fieldwork which consisted of interviewing the owner and surveying a certain number of its customers in random mode, between the questions asked to the two parties based on the accounting administration and how this is applied within the commercial Diaz. The owner of the commercial indicated that analyzes the accounting administration through the accounting books, the record of transactions or journal in which they record all the operations that they have in the establishment based on the economic part is also revised by means of the statement of profit and loss to know the feasibility of the business and how much It also regularly leaves profitability if this can be maintained in the long run. Identify how the accounting administration is kept this is rudimentary since the record is used in notebooks or sheets and even in other occasions these commercial activities are not recorded because when selling products immediately At the moment a person arrives to buy no invoice is issued so you can not know how much they have actually had in the day-to-day sales of the commercial Diaz.